Target Monitoring and Plasma Diagnosis using 2ω probe beam for CANDY. (March 2016) - Ishii, Katsuhiro; Mori, Yoshitaka; Hanayama, Ryohei; Nakayama, Suisei; Okihara, Shinichiro; Fujita, Kazuhisa; Sekina, Takashi; Sato, Nakahiro; Kurita, Takashi; Kawashima, Toshiyuki; Kan, Hirofumi; Komeda, Osamu; et al.
Abstract: We have developed the shadowgraph and interferometer with second-harmonic of heating pulses laser to observe target and plasma in highly-repetitive fusion reaction experiments. In the deuterated polystyrene ((C8 D8 ) n double foil experiment, we confirm implosion plasma and plasma collision. In target injection experiment at a 1 Hz rate, we measure the position of the flying deuterated polystyrene beads at the moment of laser pulse illumination and observe the plasma generation by counter-illumination by 0.63 J, 800 nm, and 104 fs laser pulses.